From patienthood to personhood. - Choo, Marianne Ledesma Se Se. (2009)
“From Patienthood to Personhood” is a book that seeks to explore mental illness from the viewpoint of the layman, and to document the experiences of the many PMIs and caregivers in Singapore. Specifically, our book broaches the idea that mental illness can be recovered from, as shown by stories of the PMIs within. It is different from other local publications in that it shifts the focus away from symptom management to highlight the tangible possibility of recovery, and shows that it can be generalised across different mental illnesses. Our book is not just another myth-buster or how-to manual, but a piece that our target audience of PMIs and caregivers can gain hope from. We envision our book in the health sections of bookstores like Kinokuniya and Borders. Through this, we also endeavour to show that Singaporeans with mental illness are ordinary people who live with an illness as treatable as stroke and diabetes. Such an understanding is important since mental illness may be on the rise worldwide, according to “The Global Burden of Disease” study. It predicts that conditions like depression will be among the top three causes of disease burden around the world in 2020.